Antioxidant-poisoning ZrCo hydrogen storage alloy as well as preparation method and application thereof

By doping Ce elements, ZrCo alloy is improved to form ZrCoCe alloy. Using the oxygen storage and release capacity of CeO2, the problem of oxygen poisoning in ZrCo alloy during hydrogen isotope storage is solved, and the antioxidant poisoning performance and storage efficiency of hydrogen isotopes are significantly improved.

CN119824277APending Publication Date: 2025-04-15CHINA JILIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510039918.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

ZrCo alloys are easily affected by oxygen poisoning during hydrogen isotope storage, resulting in serious deterioration in the kinetics and capacity of hydrogen absorption and release, and the prior art is difficult to effectively solve this problem.

Method used

The ZrCo alloy is improved by doping Ce elements to form a ZrCoCe alloy, which utilizes the oxygen storage and release ability of CeO2 under specific conditions to improve the antioxidant poisoning properties of the alloy.

Benefits of technology

It significantly improves the antioxidant poisoning performance of ZrCo alloy, significantly inhibits the occurrence of poisoning reactions during hydrogen absorption and discharge, and improves the efficiency of storage, supply and recycling of hydrogen isotopes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824277A_ABST
    Figure CN119824277A_ABST
Patent Text Reader

Abstract

The invention relates to the field of hydrogen storage materials and preparation and application thereof, in particular to an anti-oxygen-poisoning hydrogen storage material and a preparation method thereof, specifically, the anti-oxygen-poisoning performance of ZrCo alloy is improved by doping Ce, the composition general formula of the anti-oxygen-poisoning hydrogen storage material is ZrCoCex, x is larger than or equal to 0 and smaller than or equal to 0.1, and x represents the atomic ratio. The oxide CeO2 doped with the element Ce can store and release oxygen under specific conditions, mutual conversion of Ce < 3 + > and Ce < 4 + > is related to generation and elimination of oxygen vacancies in CeO2, and the prepared hydrogen storage material can have excellent anti-oxygen poisoning performance by means of affinity of the rare earth element Ce to oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hydrogen storage materials and their preparation, and in particular to a hydrogen storage material resistant to oxygen poisoning, a preparation method and applications thereof, and specifically to a hydrogen storage material resistant to oxygen poisoning of a ZrCo alloy improved by doping Ce, a preparation method and applications thereof. Background Art

[0002] Hydrogen is regarded as an important energy source with great prospects in the future due to its low cost, high energy density, environmental protection and renewable characteristics. It is used in aerospace, batteries, hydrogen power generation and energy vehicles. The deuterium-tritium nuclear fusion reaction can release huge energy, and it is clean, safe and efficient. In view of this, countries around the world have jointly built the International Thermonuclear Experimental Reactor (ITER) to further explore controlled nuclear fusion technology. When the reactor is in operation, the outside world needs to supply or recover hydrogen isotope gas according to actual conditions. Considering that tritium in the gas is not only very scarce, but also radioactive, therefore, the safe and efficient storage and supply of hydrogen isotope gas has become the key to the large-scale development and application of fusion energy.

[0003] There are many ways to store hydrogen and its isotopes. From the perspective of safety and efficiency, solid-state hydrogen storage technology is the preferred method that best meets the application requirements of ITER. Solid-state hydrogen storage technology can use the hydrogen cycle characteristics of materials that absorb hydrogen at low temperature and high pressure and release hydrogen at high temperature and low pressure to achieve the storage, supply and recovery of hydrogen isotope gases during the operation of ITER.

[0004] ZrCo alloy is considered to be a promising hydrogen isotope storage material for nuclear fusion reactors. However, its surface poisoning caused by impurities contained in hydrogen is a problem that needs to be overcome in engineering applications. Summary of the invention

[0005] The purpose of the present application is to provide a hydrogen storage material and a preparation method thereof for improving the anti-oxygen poisoning performance of ZrCo hydrogen storage alloy, aiming to improve the anti-oxygen poisoning performance of ZrCo hydrogen storage alloy to a certain extent.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In the first aspect, the present application provides a hydrogen storage material for improving the anti-oxidation poisoning performance of ZrCo hydrogen storage alloy, wherein the hydrogen storage alloy material is a Ce-doped ZrCo alloy, and its general composition formula is ZrCoCe x , wherein 0≤x≤0.1, and x represents an atomic ratio.

[0008] In the above technical scheme, the hydrogen storage material for improving the anti-oxygen poisoning performance of ZrCo hydrogen storage alloy provided in the first aspect of the present application is doped with Ce into the ZrCo alloy, and the oxide CeO2 doped with the element Ce can store and release oxygen under specific conditions, wherein Ce 3+ and Ce 4+ The mutual transformation is related to the generation and elimination of oxygen vacancies in CeO2, respectively. By utilizing the affinity of rare earth element Ce for oxygen, the prepared hydrogen storage alloy material can have excellent anti-oxygen poisoning properties.

[0009] In a second aspect, the present application provides a method for preparing a hydrogen storage alloy material having improved anti-oxidation poisoning performance of ZrCo alloy, comprising the following steps: (1) preparing raw materials, mixing Zr, Co, and Ce single-substance raw materials according to the atomic ratio in the chemical formula, and placing the raw materials in a magnetic suspension induction melting furnace; (2) melting, wherein the melting is carried out under the protection of an argon atmosphere; (3) cooling and solidifying, so as to obtain a ZrCoCe alloy with uniform composition. x alloy.

[0010] The second aspect of the present application provides a method for preparing a hydrogen storage material that improves the anti-oxidation poisoning performance of ZrCo hydrogen storage alloy. After the raw materials are prepared, they are placed in a magnetic levitation vacuum melting furnace. The furnace body is suspended in the air by an electromagnetic field using magnetic levitation technology, which reduces mechanical friction and thermal stress, thereby improving the purity and uniformity of the alloy metal material. The smelting is carried out under the protection of an inert gas argon atmosphere, so that the product ZrCoCe x The alloy has good morphology and excellent interface.

[0011] In combination with the second aspect, in some possible implementations, the pressure of the argon gas is 1.2 to 1.4 bar. In this way, the obtained product ZrCoCe x The alloy has a stable structure and excellent performance. There are ZrCo phase and CeO2 phase on its surface. The two have good matrix bonding and have excellent anti-oxidation poisoning performance.

[0012] In combination with the second aspect, in some possible implementations, the smelting temperature is 1800-2300° C., and the smelting time is 45-60 s.

[0013] In combination with the second aspect, in some possible implementations, the smelting temperature is 1800-2300°C.

[0014] In combination with the second aspect, in some possible embodiments, step (2) and step (3) may be repeated 3 to 5 times, wherein the pressure of the argon gas is independently selected to be 1.2 to 1.4 bar, and / or the smelting time is independently selected to be 45 to 60 s, and / or the smelting temperature is independently selected to be 1800 to 2300°C.

[0015] On the third aspect, the oxygen-resistant ZrCo hydrogen storage alloy described in the present application can be applied to the storage, supply and recovery of hydrogen isotopes.

[0016] In combination with the third aspect, in some possible embodiments, the hydrogen isotopes include one or more of protium, deuterium, and tritium.

[0017] The alloy ingot prepared in the present application presents a flaky nanostructure after activation, with a uniform ZrCo composition, Ce dispersed in the alloy in the form of Ce and CeO2, and a ZrCo phase and a CeO2 phase with oxygen vacancies on the surface, which has excellent anti-oxygen poisoning performance and can significantly inhibit the occurrence of ZrCo poisoning reactions during hydrogen absorption and desorption, thereby achieving the storage, supply, and recovery of hydrogen isotopes. Not only that, the doping of Ce in the present application has the effect of deoxidation, making the content of ZrCo2 impurity phase less, and Ce also plays a certain role in grain refinement, which improves the activation performance of ZrCo. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 is the XRD spectrum of the hydrogen storage alloys of Examples 1 to 3 of the present application and Comparative Example 1;

[0020] Figure 2 is a schematic diagram of the SEM morphology of the cast alloy of the hydrogen storage material provided in Example 2 of the present application;

[0021] Figure 3 is an energy spectrum diagram of the cast alloy of the EDS hydrogen storage alloy provided in Example 2 of the present application;

[0022] Figure 4 Schematic diagram of hydrogen absorption cycle performance of hydrogen storage alloy materials provided in Comparative Example 1 and Example 2 of the present application;

[0023] Figure 5 1 is a schematic diagram comparing the test results of the hydrogen absorption and desorption cycle stability performance of the hydrogen storage alloy materials provided in Comparative Example 1 and Example 2 of the present application;

[0024] Figure 6 This is a schematic diagram of the structure of the hydrogen storage alloy material before and after the hydrogen absorption and desorption cycle provided in Example 2 of the present application;

[0025] Figure 7This is a schematic diagram of the XPS test results of the hydrogen storage alloy provided in Example 2 of the present application.

[0026] Figure 8 The hydrogen absorption performance curve of the hydrogen storage alloy material provided in Examples 1 to 3 of the present application and Comparative Example 1 is DETAILED DESCRIPTION

[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0028] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0029] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0030] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0032] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0033] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0034] In practical applications of reactors, hydrogen isotope gas requires controllable supply and recovery technology. Given the radioactivity and scarcity of tritium, a safe and effective hydrogen isotope storage and delivery system (SDS) is needed to prevent it from leaking into the surrounding atmosphere. Researchers use safe and efficient solid-state hydrogen storage technology as the implementation technology for hydrogen isotope recovery, storage and supply. ZrCo-based alloys have outstanding hydrogen absorption and desorption kinetics, extremely low room temperature equilibrium pressure (10 -3 pa), non-radioactivity and excellent He capture performance, and is considered to be an important candidate material for hydrogen isotope storage, supply and recovery.

[0035] The engineering application of ZrCo-based alloys is easily affected by the negative impact of surface poisoning caused by O2. This is mainly due to the violent combustion of plasma. In the nuclear fusion system, a small amount of O2 will inevitably accumulate and mix in the hydrogen isotope gas, which seriously deteriorates the hydrogen absorption and desorption kinetics and hydrogen absorption and desorption capacity of ZrCo-based alloys. There are some methods for improving the anti-poisoning performance of ZrCo hydrogen isotope storage alloys in this field, mainly focusing on surface coating methods, but the degree of anti-poisoning improvement is small or the operation process is complicated, and it is impossible to meet the requirements in practice. In surface coating, complex operations are often required to coat the alloy with the required protective layer, and the modified alloy often causes the protective layer to fall off due to repeated expansion and contraction of the volume during the cyclic absorption and desorption of hydrogen, thereby causing the alloy to lose its anti-poisoning effect.

[0036] Alloying is a strategy to improve the poisoning resistance of ZrCo alloys, and the self-sacrificial effect of doping elements on impurity gases can be used for anti-poisoning modification. However, due to the limited content of doping elements and their tendency to poison, the self-sacrificial effect will gradually weaken as the hydrogen absorption and desorption cycle proceeds in an impurity-containing atmosphere. Designing suitable doping elements and constructing effective surface and interface structures to restore the self-sacrificial ability of materials are strong requirements for ZrCo alloys to achieve and maintain excellent anti-poisoning capabilities. There is no systematic research and theoretical guidance on the cyclic stability of ZrCo-based alloys under hydrogen and oxygen mixtures in the related art. The inventors of this application have studied the alloying modification of ZrCo to improve its anti-poisoning performance, so as to better apply it in the field of hydrogen isotopes, including but not limited to the storage, supply, and recovery of hydrogen isotopes, which is of great significance.

[0037] Specifically, the present application provides a hydrogen storage material and a preparation method thereof for improving the O2 poisoning resistance of ZrCo hydrogen storage alloy by doping Ce, which can solve the problem of poor O2 poisoning resistance of ZrCo-based hydrogen isotope storage alloy to a certain extent. The hydrogen storage material is a Ce-doped ZrCo alloy, and its general composition formula is ZrCoCe x , where 0≤x≤0.1, and x represents the atomic ratio. The method for preparing the hydrogen storage material for improving the anti-oxidation poisoning performance of the ZrCo hydrogen storage alloy comprises the following steps: (1) preparing raw materials, mixing Zr, Co, and Ce single-substance raw materials according to the atomic ratio in the chemical formula, and placing them in a magnetic suspension induction melting furnace; (2) melting, wherein the melting is carried out under the protection of an argon atmosphere; (3) cooling and solidifying, so as to obtain a ZrCoCe with uniform composition. x Specifically, the raw materials include weighing Zr, Co, and Ce raw materials with a purity of more than 99.95% in the atomic percentage of 1:1:x, mixing them evenly and placing them in the water-cooled copper crucible pit of the magnetic suspension induction melting furnace to make the vacuum degree reach 3×10 -3The smelting is carried out under the protection of an inert gas argon atmosphere, and after smelting, the alloy is cooled and solidified to obtain the ZrCo-Ce hydrogen isotope storage alloy with excellent oxidation resistance. Optionally, the pressure of the argon gas is 1.2 to 1.4 bar. The inert gas argon atmosphere protection is mainly used to prevent air infiltration. Other inert gases, such as helium, neon, etc., can be selected for atmosphere protection, which is not limited here. Optionally, the smelting temperature is 1800-2200°C, and the time is 45-60s, wherein the melting and boiling points of Zr are 1852°C and 4377°C, respectively, the melting and boiling points of Co are 1495 and 2870°C, respectively, and the melting and boiling points of Ce are 795 and 3443°C, respectively. If the smelting time is too short or the temperature is too low, some elements will not be completely melted and the various components will be mixed unevenly. If the smelting time is too long or the temperature is too high, it will cause element burnout and the composition will deviate from the design. Based on the melting and boiling point data of Zr, Co, and Ce, the appropriate smelting temperature and time are selected. On the one hand, the smelting time can be saved, and more importantly, a structurally stable and uniform alloy metal material can be obtained. Optionally, the smelting and cooling and solidification operations can be repeated 3-5 times to obtain the ZrCo-based hydrogen isotope storage alloy with excellent anti-oxidation poisoning performance to ensure the uniformity of the alloy composition. During the repeated smelting and cooling and solidification operations, the alloy can be turned over.

[0038] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the hydrogen storage material and its preparation method for improving the anti-oxidation poisoning performance of ZrCo alloy in the embodiments of the present application, the above technical scheme is illustrated by means of multiple embodiments below.

[0039] Example 1

[0040] A hydrogen storage material for improving the anti-oxidation poisoning performance of ZrCo hydrogen storage alloy, the chemical composition of which is ZrCoCe 0.025 , the preparation of which comprises the steps of:

[0041] 1. Prepare the raw materials, and calculate the addition amount of Zr, Co, and Ce single-substance raw materials according to the atomic ratio (molar ratio) of Zr, Co, and Ce of 1:1:0.025. The purity of the single-substance raw materials of Zr, Co, and Ce used is more than 99%. After the raw materials are cleaned and dried, they are weighed according to the calculated addition amount.

[0042] 2. Melting: Place the weighed raw materials in a water-cooled copper crucible of a magnetic suspension induction melting furnace, evacuate the air to a vacuum degree of <0.1 Pa, and then melt them under the protection of an argon atmosphere of 1.2 bar. The melting temperature is 1800°C and the melting time is 60 seconds.

[0043] 3. Cool and solidify, and cool naturally under the protection of argon atmosphere.

[0044] 4. Repeat steps 2 and 3 four times to obtain ZrCoCe with uniform composition. 0.025 The hydrogen isotope storage alloy ingot is the hydrogen isotope storage alloy.

[0045] Example 2

[0046] A hydrogen storage material for improving the anti-oxidation poisoning performance of ZrCo hydrogen storage alloy, the chemical composition of which is ZrCoCe 0.05 , the preparation of which comprises the steps of:

[0047] 1. Prepare the raw materials, and calculate the addition amount of Zr, Co, and Ce single-substance raw materials according to the atomic ratio (molar ratio) of Zr, Co, and Ce of 1:1:0.05. The purity of the single-substance raw materials of Zr, Co, and Ce used is more than 99%. After the raw materials are cleaned and dried, they are weighed according to the calculated addition amount.

[0048] 2. Melting: Place the weighed raw materials in a water-cooled copper crucible of a magnetic suspension induction melting furnace, evacuate the air to a vacuum degree of <0.1 Pa, and then melt them under the protection of an argon atmosphere of 1.2 bar. The melting temperature is 1800°C and the melting time is 60 seconds.

[0049] 3. Cool and solidify, and cool naturally under the protection of argon atmosphere.

[0050] 4. Repeat steps 2 and 3 four times to obtain ZrCoCe with uniform composition. 0.05 The hydrogen isotope storage alloy ingot is the hydrogen isotope storage alloy.

[0051] Example 3

[0052] A hydrogen storage material for improving the anti-oxidation poisoning performance of ZrCo hydrogen storage alloy, the chemical composition of which is ZrCoCe 0.1 , the preparation of which comprises the steps of:

[0053] 1. Prepare the raw materials, and calculate the addition amount of Zr, Co, and Ce single-substance raw materials according to the atomic ratio (molar ratio) of Zr, Co, and Ce of 1:1:0.1. The purity of the single-substance raw materials of Zr, Co, and Ce used is more than 99%. After the raw materials are cleaned and dried, they are weighed according to the calculated addition amount.

[0054] 2. Melting: Place the weighed raw materials in a water-cooled copper crucible of a magnetic suspension induction melting furnace, evacuate the air to a vacuum degree of <0.1 Pa, and then melt them under the protection of an argon atmosphere of 1.2 bar. The melting temperature is 1800°C and the melting time is 60 seconds.

[0055] 3. Cool and solidify, and cool naturally under the protection of argon atmosphere.

[0056] 4. Repeat steps 2 and 3 four times to obtain ZrCoCe with uniform composition. 0.1 The hydrogen isotope storage alloy ingot is the hydrogen isotope storage alloy.

[0057] Comparative Example 1

[0058] A ZrCo hydrogen storage alloy hydrogen storage material is different from the embodiment in that Ce is not doped and other preparation steps and parameters remain unchanged.

[0059] Further, in order to verify the progress of the embodiments of the present application, the following performance tests were performed on the hydrogen storage materials of the alloys prepared in embodiments 1 to 3 of the present application and comparative example 1:

[0060] 1. Through XRD ray diffraction analysis, such as Figure 1 The XRD patterns of the hydrogen isotope storage alloys prepared in Comparative Example 1 and Examples 1 to 3 are shown. As shown in the figure, the ZrCo alloy consists of the main phase ZrCo and a small amount of ZrCo2. As the Ce content in the ZrCo alloy increases, the proportion of the Ce phase and CeO2 phase in the alloy gradually increases, and the peak intensity of the ZrCo2 phase decreases significantly. It can be seen that the presence of Ce in the alloy plays a key role in its phase composition.

[0061] 2. The cast alloy of the hydrogen storage material in Example 2 was subjected to a scanning electron microscope (SEM) test to study the effect of Ce doping on the microscopic characteristics of the ZrCo alloy. Generally, the cast state refers to the microstructure formed after the metal (mostly alloy) material is transformed from a metal melt into a solid (casting) during the smelting process. The test results are as follows: Figure 2 As shown. Figure 2 (a) Alloy at 40 μm size and Figure 2 (b) is the SEM morphology of the alloy at 10 μm size. From the gray and white areas in the figure, it can be seen that there is a multiphase structure on the alloy surface ( Figure 2 The circled part in b is the surface state of Ce phase).

[0062] 3. The cast alloy in Example 2 was tested by EDS, and the microscopic characteristics and evolution of the ZrCo alloy after Ce doping were analyzed by SEM. Figure 3 The corresponding EDS spectrum shows that the distribution of Zr, Co, Ce and O elements is unique. Among them, Zr and Co elements are basically present in the gray phase, while Ce and O elements are basically present in the white phase. At the same time, the material within the dotted line is mainly Ce element without O element, indicating that there is a trace amount of Ce element that has not been oxidized. The above phenomenon shows that ZrCo is uniform, and the Ce-containing phase is dispersed in the form of segregation to the ZrCo surface.

[0063] 4. Test the hydrogen absorption cycle performance of hydrogen storage alloy materials in an oxygen-containing atmosphere.

[0064] The sample needs to be activated and dehydrogenated first. Specifically, the ZrCo in Comparative Example 1 and the ZrCoCe in Example 2 are first 0.05 After the surface of the ingot is cleaned and polished, it is placed in a stainless steel sealed container and continuously evacuated at 500°C for half an hour. After the evacuation is completed, when the furnace is cooled to 100°C, 5 bar of high-purity hydrogen is filled into the container to fully absorb hydrogen and activate the ingot, and completely break it into powder samples to obtain hydrogen-absorbing powders. Subsequently, the obtained hydrogen-absorbing powders are respectively loaded into a stainless steel sealed reactor, and the reactor is heated to 600°C at a heating rate of 10°C / min and kept warm for 1h, and then cooled to room temperature with the furnace. During this period, the reactor is continuously evacuated to obtain active and completely dehydrogenated ZrCo and ZrCoCe 0.05 The samples were then subjected to hydrogen absorption tests at different oxygen concentrations.

[0065] The hydrogen absorption conditions are room temperature (25°C), total pressure 1.2 bar, gas composition 99 mol% H2+1 mol% O2, 98 mol% H2+2 mol% O2, 97 mol% H2+3 mol% O2. The hydrogen absorption operation is carried out under the above conditions, and the hydrogen absorption curve is as follows: Figure 4 As shown in the figure, the horizontal axis represents time and the vertical axis represents capacity percentage. Figure 4 As shown in Figure 2, under the mixed gas of 99 mol% H2+1 mol% O2, ZrCo needs nearly 3 h to reach the saturated hydrogen absorption capacity of 1.7074 wt%, while ZrCoCe 0.05 It only takes about 72 seconds to absorb 1.7596wt% of the capacity, and reaches a saturated hydrogen absorption capacity of 1.8986wt% after 0.5h. With the increase of oxygen concentration, the hydrogen absorption performance of ZrCo alloy has obviously declined significantly, while the alloy with Ce added can still maintain good kinetic properties and saturated hydrogen absorption capacity. This proves that the Ce phase in the hydrogen storage alloy can act as a self-sacrificing element to preferentially absorb oxygen to avoid further oxidation of ZrCo.

[0066] 5. The hydrogen absorption and desorption cycle stability performance test is an important indicator for ITER to screen hydrogen isotope storage and supply alloys. The active completely dehydrogenated samples prepared in Comparative Example 1 and Example 2 were subjected to hydrogen absorption and desorption cycle tests respectively.

[0067] Specifically, the hydrogen absorption conditions during the cycle test were room temperature (25°C), total pressure 1.2 bar, gas composition 99 mol% H2 + 1 mol% O2, and the hydrogen release conditions were to release hydrogen from the vacuum chamber at 380°C. The cycle operation was performed under the above conditions to obtain the cycle hydrogen absorption capacity diagram as shown in the figure below: Figure 5As shown, the horizontal axis indicates the number of cycles and the vertical axis indicates the capacity (percentage). ZrCo and ZrCoCe 0.05 The initial hydrogen absorption capacity of the samples was 1.707wt% and 1.899wt% respectively. After three cycles, the ZrCo sample no longer absorbed hydrogen, indicating that its poisoning was serious. 0.05 The hydrogen absorption capacity of the sample after ten cycles can still reach 1.376wt%, and the cycle capacity retention rate is 72.5%. 0.05 The cyclic stability of the alloy is much better than that of ZrCo alloy, which is derived from the reversible self-sacrificial effect of CeO2 with oxygen vacancies produced after cyclic dehydrogenation and its catalytic effect on H2.

[0068] 6. Test on the change of phase structure before and after hydrogen absorption and desorption cycles, to show the change of phase structure of the hydrogen storage alloy of the present application before and after hydrogen absorption and desorption cycles in impurity gas. Specifically, XRD test was performed on the first and tenth hydrogen absorption samples of the hydrogen storage alloy in Example 2 under impurity gas, and the test results are as follows: Figure 6 It can be found that after ten cycles, the content of CeO2 phase increases sharply, and CeH 2.73 The content of Ce phase is relatively reduced, while the main phase of the alloy is still ZrCo phase. The above results further prove that the high adsorption of Ce phase to oxygen can effectively reduce the oxidation of ZrCo.

[0069] 7. The cast alloy in Example 2 was subjected to an X-ray photoelectron spectroscopy (XPS) test to further verify that the ZrCo-based alloy induced CeO2 to form oxygen vacancies during the dehydrogenation process. The test results are as follows: Figure 7 As shown, the horizontal axis indicates the binding energy (in electron volts) and the vertical axis indicates the intensity. Figure 7 As shown in the figure, the O peaks near 530eV, 531eV and 533eV are lattice oxygen (OL), vacancy oxygen (OV) and adsorbed oxygen (OA), respectively. After ten cycles, the concentration of OV accounts for 38.11% of the total, which shows that there are still some oxygen vacancies on the surface after the cycle. However, after dehydrogenation of the sample after ten cycles, its OV increased to 53.69%, which means that during the high-temperature dehydrogenation process, the lattice oxygen in CeO2 will break away from the original binding position to form oxygen vacancies.

[0070] 8. As Figure 8The hydrogen absorption performance curves of the hydrogen storage alloy materials provided in Examples 1 to 3 and Comparative Example 1 of the present application are shown in the figure. As shown in the figure, the hydrogen absorption performance curves of the above four alloys under 1 mol% O2 show that doping Ce in ZrCo can significantly improve its oxidation resistance. On the one hand, for the saturated hydrogen absorption capacity, Ce 0.025 and Ce 0.05 Alloy is excellent, but Ce 0.025 The hydrogen absorption kinetics of Ce is relatively slow. 0.05 and Ce 0.1 Alloy is excellent, but Ce 0.1 The saturated hydrogen absorption capacity is relatively low. In summary, the ratio of Ce doping can be selected according to actual needs. In this application, Ce is selected mainly for comparison and explanation. 0.05 The alloy was used as an example for experimental verification.

[0071] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A ZrCo hydrogen storage alloy resistant to oxygen poisoning, characterized in that: The general formula of the hydrogen storage alloy is ZrCoCe x , where x represents an atomic ratio.

2. The ZrCo hydrogen storage alloy resistant to oxygen poisoning according to claim 1, characterized in that: In the general composition formula, 0≤x≤0.

1.

3. The ZrCo hydrogen storage alloy resistant to oxygen poisoning as claimed in claim 2, characterized in that: The value of x in the general composition formula is 0.025≤x≤0.

05.

4. A method for preparing a ZrCo hydrogen storage alloy resistant to oxygen poisoning, characterized in that: The method comprises the following steps: (1) preparing raw materials, mixing Zr, Co and Ce single-substance raw materials according to the atomic ratio in the chemical formula, and placing the raw materials in a magnetic suspension induction melting furnace; (2) melting, wherein the melting is carried out under the protection of an argon atmosphere; (3) cooling and solidifying, thereby obtaining ZrCoCe x alloy.

5. The method for preparing the oxygen-poisoning-resistant ZrCo hydrogen storage alloy according to claim 4, characterized in that: The pressure of the argon gas is 1.2-1.4 bar.

6. The method for preparing the oxygen-poisoning-resistant ZrCo hydrogen storage alloy according to claim 4, characterized in that: The smelting temperature is 1500-2600° C., and the smelting time is 45-60 seconds.

7. The method for preparing the oxygen-poisoning-resistant ZrCo hydrogen storage alloy according to claim 5, characterized in that: The smelting temperature is 1800-2300°C.

8. The method for preparing the oxygen-poisoning resistant ZrCo hydrogen storage alloy according to any one of claims 4 to 7, characterized in that: Repeat step (2) and step (3) 3 to 5 times, wherein the pressure of the argon gas is independently selected to be 1.2 to 1.4 bar, and / or the smelting time is independently selected to be 45 to 60 s, and / or the smelting temperature is independently selected to be 1800 to 2300°C.

9. Use of any oxygen-poisoning-resistant ZrCo hydrogen storage alloy according to claims 1 to 3 and the oxygen-resistant ZrCo hydrogen storage alloy prepared according to the method of claims 4 to 8 in the storage, supply and recovery of hydrogen isotopes.

10. The use according to claim 9, characterized in that: The hydrogen isotopes include one or more of protium, deuterium and tritium.

Citation Information

Patent Citations

  • Rare earth Ce doping titanium-chromium-vanadium-manganese solid solution hydrogen occluding alloy

    CN101435049A

  • Hydrogen isotope storage alloy and preparation method thereof

    CN108330323A

  • Oxygen poisoning resistant hydrogen storage alloy and preparation method thereof

    CN112391568A

  • Activation-free high-capacity magnesium-based hydrogen storage alloy and preparation method thereof

    CN116516192A

  • Composite hydrogen storage material with high poisoning resistance and preparation method thereof

    CN120288706A